Water Balance Analysis and Embung-Long Storage Planning as a Technical Irrigation Solution for Rainfed Paddy Fields in Padang Kunik Village, Kuantan Singingi Regency - Desvi Mardiah Darma; Sri Wahyuni; Tri Budi Prayogo (Jurnal Penelitian Pendidikan IPA, 2026)
Rainfed paddy fields relying entirely on rainfall are vulnerable to seasonal water deficits and limited to one planting season per year (Cropping Index/CI 100). This study analyzed the water balance of 77 ha of rainfed paddy land in Padang Kunik Village, Kuantan Singingi Regency, and formulated a technical storage solution to improve irrigation water availability. Water availability was calculated using the Simple Water Balance method with 20 years of rainfall data (2006–2025) from three rain gauges, while irrigation demand followed KP-01 guidelines. The Ripple (mass-curve) method determined the required Effective Storage Capacity. Results showed deficits in seven separate periods, with a cumulative peak deficit of 140,647.00 m³ in April I and a total required storage volume, after accounting for evaporation, seepage, and sediment losses, of 175,077.41 m³. A combination of an embung (172,800.00 m³ on 4.3 ha of non-productive land) and 4,562 m of long storage was planned, yielding a total volume of 177,362.00 m³, or 101% of the requirement, distributable to the paddy fields by gravity given the elevation difference. The proposed system is technically feasible to eliminate seasonal deficits and could raise the Cropping Index from CI 100 to CI 200.